The influence of al-Sahihayn on popular hadith literatures: The case of Khazinah al-AsrarJalilah al-Adhkar - Abdullah W.H.; Borham A.H.; Hashim A.; Muhammad Mustaqim Mohd.Zarif (Kolej University Islam Sultan Azlan Shah, 2024)
Indexed by SCOPUS